The drowning spool eaudiobook A needlecraft mystery. - Ferris, Monica (Needlecraft Mystery, 2014)
Even though running Crewel World keeps Betsy plenty busy, a little extra cash on the side doesn't hurt. So when the local senior complex, Watered Silk, asks her to teach a class on the tricky punch needle technique, Betsy jumps at the opportunity to win over some new customers. Unfortunately, the business that Betsy drums up is not of the needlework variety. A young woman is found floating in Watered Silk's therapy pool, and Betsy's sleuthing skills are immediately called upon to figure out who drowned her. But the list of suspects is more twisted than any Betsy has encountered before. The young woman had three lovers - each with a motive for the murder. It's up to Betsy to sort out the snarl of romantic entanglements and find a killer.